2022
DOI: 10.48550/arxiv.2201.07627
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implicit Tracking-based Distributed Constraint-coupled Optimization

Jingwang Li,
Housheng Su

Abstract: In this work, a kind of distributed constraintcoupled optimization problem is studied. We first propose an augmented primal-dual dynamics and study its convergence, but the need for knowing the violation of the coupled constraint prevents it from being implemented distributedly. By comprehending a classical continuous-time distributed optimization algorithm from a new perspective, the novel implicit tracking approach is proposed to track the violation distributedly, which leads to the implicit tracking-based d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Though they do not possess the explicit gradient tracking structure, we found that they do have an implicit one, hence they can also be seen as gradient tracking algorithms, but with the implicit tracking approach. The implicit tracking mechanism (approach) is first proposed in [18], which is employed to develop efficient algorithms for distributed constraint-coupled optimization problems. Specifically speaking, [18] offers a new perspective to understand a classical continuous-time distributed optimization algorithm [20], which is given as…”
Section: Unified Gradient Trackingmentioning
confidence: 99%
See 4 more Smart Citations
“…Though they do not possess the explicit gradient tracking structure, we found that they do have an implicit one, hence they can also be seen as gradient tracking algorithms, but with the implicit tracking approach. The implicit tracking mechanism (approach) is first proposed in [18], which is employed to develop efficient algorithms for distributed constraint-coupled optimization problems. Specifically speaking, [18] offers a new perspective to understand a classical continuous-time distributed optimization algorithm [20], which is given as…”
Section: Unified Gradient Trackingmentioning
confidence: 99%
“…The implicit tracking mechanism (approach) is first proposed in [18], which is employed to develop efficient algorithms for distributed constraint-coupled optimization problems. Specifically speaking, [18] offers a new perspective to understand a classical continuous-time distributed optimization algorithm [20], which is given as…”
Section: Unified Gradient Trackingmentioning
confidence: 99%
See 3 more Smart Citations